Right Atrial Appendage Aneurysm in a Newborn Diagnosed with Fetal Echocardiography - Helen Bornaun; Elif Yartaşı Tik; Gonca Keskindemirci; Ali Ekiz; Kazım Öztarhan; Reyhan Dedeoğlu; Merih Çetinkaya (Case Reports in Pediatrics)
Right atrial appendage aneurysm is a very rare condition which can be asymptomatic or can cause arrhythmia or life-threatening thromboembolism. We report a case of newborn with right atrial appendage aneurysm who was diagnosed with fetal echocardiography. Anticoagulant therapy was applied to prevent thromboembolism and he is still going on follow-up without any complaint.